#TITLE_ALTERNATIVE# - SAMPE TOLA (NIM 10204022); Pembimbing: Rahmat Hidayat, Ph.D., PARDI
This thesis presented the experimental results on the fabrication of inorganicorganic hybrid polymer doped with organic dye laser, Rhodamine 6G, molecules using sol-gel method and the characterization of their optical properties. Those characterizations are the measurement of the absorbtion spectrum using Attenuated Total internal Reflection method, the refraction index using reflectance method, and their molecular structure using FTIR spectrometer. The hybrid polymer fabrication has been carried out by sol-gel method using 3-(trimethoxysily) propyl methacrylate, ethanol, acid catalyst, H2O, and Rhodamine 6G. The characterization result of the gel precursor shows the formation of inorganic network Si-O-Si. The foemation of organic croslinking has been achiaved by UV-curing reaction (photopolymerization) using photoinisiator Irgacure-369. This hybrid poymer has the refraction indeks of about 1.4.